Physiotherapy in the motor development of premature neonates in the Neonatal Intensive Care Unit (Research, Society and Development, 2024)
Premature birth occurs before 37 weeks of gestation, resulting in possible neuropsychomotor delays in children, thus motor stimulation becomes a fundamental part of the evolution of development, in addition to organizing body systems. The objective of the study is to describe, through an integrative review, the role of physiotherapy in the motor development of premature newborns in the Neonatal Intensive Care Unit. This study is an integrative review, where the Scielo, PubMed and VHL databases were consulted. The results obtained were that the physiotherapist plays a crucial role in contributing to the motor development of newborns, through objective approaches aimed at the patient's clinical needs, preventing future neuropsychomotor dysfunctions and promoting development close to typical childhood standards. It is concluded through the study that the physiotherapist working in the Neonatal Intensive Care Unit works with a central focus on preventing future neuropsychomotor dysfunctions, through stimulation strategies, to ensure an evolution close to typical patterns of child development milestones.